GAMBARAN PARASIT INTESTINAL PADA PASIEN KANKER KOLOREKTAL DI RSUP DR M DJAMIL PADANG TAHUN 2023 - Nurul Arbaniah; Nuzulia Irawati; Firdawati; Selfi Renita Rusjdi; Avit Suchitra; Gusti Revilla (SINERGI : Jurnal Riset Ilmiah, 2026)
Colorectal cancer is the third most common malignancy in the world, disturbing normal cell control and mechanism and damaging immune system, therefore the susceptibility to parasitic infection is increasing. The aim of this study was to determine the incidence of intestinal parasitic infections in colorectal cancer patients at RSUP Dr. M. Djamil Padang. This is a categorical descriptive study from primary data with a total sample of 65 colorectal cancer patients using consecutive sampling technique. This research uses univariate analysis and is presented in the form of a frequency distribution table. The results of the study showed that intestinal parasitic infections in colorectal cancer patients amounted to 47,7% (31/65) with intestinal parasites found Cryptosporidium sp. of 61,9% (26/42) and Blastocystis sp. 30,9% (13/42). Intestinal parasitic infections were higher in the age group of <40 years by 80% (12/31) and higher in male patients by 54,8% (17/31). The most common type of infection is single infection, amounting to 71% (22/31). Incidence of intestinal parasitic infections is quite high in colorectal cancer patients at RSUP Dr. M. Djamil Padang. Colorectal cancer patients need to be screened and considered given antiparasitic drugs as well as education about preventing diseases caused by intestinal parasites